A novel Lyapunov-based robust controller design for LCL-type shunt active power filters using adaptive sliding-mode backstepping approach - Vadood Hajbani; Adel Zakipour; Mahdi Salimi (e-Prime: Advances in Electrical Engineering, Electronics and Energy, 2023)
In this paper, a novel hybrid two-loop nonlinear controller is designed for stabilization and robust control of the LCL-type shunt active power filter (SAPF). To cope with the instability issue of the closed-loop system and the inherent resonance of the LCL coupling, backstepping, sliding mode and adaptive controllers are combined. DC link voltage of the grid-connected inverter is regulated in an outer control loop by determining a proper reference value for an inner loop. In addition to DC link voltage control, a major objective of the proposed closed-loop system is to make the grid current in phase with the grid voltage directly. Hence, active power filtering of the grid-connected inverter can be achieved without any current feedback from the local load. To stabilize the LCL-type SAPF in a wide range of changes, all uncertain parameters of the model including the DC link capacitor and equivalent impedances of the LCL coupling network are estimated by employing a proper Lyapunov function. For practical evaluation of the developed approach, the closed-loop system is implemented by using Texas Instruments’ digital signal processor (DSP-TMS28F335). Considering the application of an adaptive-robust nonlinear controller, it is proved that the system enjoys a stable and robust performance over the whole range of utilization, and it doesn't suffer from resonance issues of the LCL-type SAPFs. Moreover, considering the experimental results, it is observed that the steady-state error of the proposed nonlinear controller is zero in a wide range of operations.